Sense of Community for Nature Lover Student Organization (MAPALA) Members: Rasa Kebersamaan pada Anggota Organisasi Mahasiswa Pecinta Alam (MAPALA) - Pratama, Andi; Maryam, Effy Wardati (Indonesian Journal of Innovation Studies, 2023)
This research was conducted because there were problems related to the level of sense of community in members of nature lovers student organizations (mapala) in Sidoarjo regency. These problems are like members who are lazy in activities, do not want to help other members, feel that the organization does not live up to its expectations finally decide to leave the organization, there is seniority and juniority in the organization. Those are some of the problems found in members of nature lover students (mapala) in Sidoarjo regency. The purpose of this study is to find out the picture of the level of sense of community in members of nature lovers student organizations (mapala) in Sidoarjo regency. This research is descriptive quantitative research. The sample in this study was all members of nature lovers student organizations in Sidoarjo regency as many as 103 people. Data retrieval techniques use a sense of community scale arranged with the Likert scale. This research data analysis technique uses descriptive statistical techniques. The results of this study showed that 57 out of 103 people had a sense of community with a high category (55.3%), 16 out of 103 people had a sense of community with a low category (15.5%), 9 out of 103 people had a sense of community with a medium category (8.7%).